Intraoperative Evaluation of Body Surface Improvement by an Augmented Reality System That a Clinician Can Modify. Issue 8 (August 2017) - Mitsuno, Daisuke; Ueda, Koichi; Itamiya, Tomoki; Nuri, Takashi; Otsuki, Yuki
Abstract : Background: Augmented reality (AR) technology that can combine computer-generated images with a real scene has been reported in the medical field recently. We devised the AR system for evaluation of improvements of the body surface, which is important for plastic surgery. Methods: We constructed an AR system that is easy to modify by combining existing devices and free software. We superimposed the 3-dimensional images of the body surface and the bone (obtained from VECTRA H1 and CT) onto the actual surgical field by Moverio BT-200 smart glasses and evaluated improvements of the body surface in 8 cases. Results: In all cases, the 3D image was successfully projected on the surgical field. Improvement of the display method of the 3D image made it easier to distinguish the different shapes in the 3D image and surgical field, making comparison easier. In a patient with fibrous dysplasia, the symmetrized body surface image was useful for confirming improvement of the real body surface. In a patient with complex facial fracture, the simulated bone image was useful as a reference for reduction. In a patient with an osteoma of the forehead, simultaneously displayed images of the body surface and the bone made it easier to understand these positional relationships. Conclusions: This study confirmed that AR technology is helpful for evaluation of the body surface in several clinical applications. Our findings are not only useful for body surface evaluation but also for effective utilization of AR technology in the field of plastic surgery.